EVALUASI SISTEM INFORMASI AKUNTANSI ATAS PENJUALAN KREDIT PT. XYZ (DEALER RESMI MITSUBISHI CABANG SEMARANG) - Hesti Fajarsari; Henry Anggoro Djohan; Andreas Setiawan; Martini Martini (LPPM Universitas Bina Insan, 2020)
This study to evaluate the application of accounting information system of credit sales in an effort to improve internal control that has been carried out by PT. XYZ (Mitsubishi Official Dealer Semarang Branch) is a company engaged in the trading business. The method used in this research is descriptive qualitative method using data collection techniques such as observation, interviews, and documentation. The results showed that the accounting information system of credit sales implemented by PT. XYZ (Mitsubishi Official Dealer Semarang Branch) has presented the information needed by the company precisely and accurately although there are still weaknesses that need to be addressed, like the separation of cash receipts and recording functions, and the separation of sales admin and stock admin functions. But overall internal control at PT. XYZ (Mitsubishi Official Dealer Semarang Branch) is adequate because it meets the elements of internal control.